A 3 Terminal Parallel Connected Silicon Tandem Solar Cell. (August 2016) - Jimeno, Juan. C.; Gutierrez, Rubén; Fano, Vanesa; Habib, Ahmed; del Cañizo, Carlos; Rasool, Muhammad A.; Otaegi, Aloña
Abstract: A new tandem structure based on a silicon solar cell is presented. This structure works with two or three junction levels, being the silicon cell in this last case the intermediate cell. The different levels have been interconnected in parallel and for that a greater number of the lower band gap cells would be needed in order to equalize the operating voltage of all the structure. However, the presented three terminals structure only needs a maximum of 4 pn junctions for the 3 levels structure or even only 2 for a two level structure. This structure can be easily included in a conventional 2 terminal flat module without complicating the internal wiring. The maximum technological efficiency has been estimated in 39.4% for the three levels structure and using well known materials for each level a 30 to 32% efficiency level sounds possible.